Weight Management 2020
DOI: 10.5772/intechopen.92589
|View full text |Cite
|
Sign up to set email alerts
|

A Software-Assisted Qualitative Study on the Use of Music in People with Anorexia Nervosa

Abstract: Anorexia nervosa (AN) is an eating disorder associated with a high mortality and an often chronic and disabling course. Thus, novel treatment options should be explored. We performed two focus groups with a total of six people with AN on their use of music and their thoughts about music as an additional therapeutic option. Interviews were transcribed and analyzed in-depth using the NVivo 12 software package. The most prevalent theme throughout the focus groups involved positive expressions, emotions and memori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…To evaluate patients' attitudes surrounding music and music therapy, we developed a questionnaire based on a preparatory study (13). The questionnaire comprised of 50 questions split into seven sections: Section one and two provided patient information, such as age, sex, and duration of illness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate patients' attitudes surrounding music and music therapy, we developed a questionnaire based on a preparatory study (13). The questionnaire comprised of 50 questions split into seven sections: Section one and two provided patient information, such as age, sex, and duration of illness.…”
Section: Methodsmentioning
confidence: 99%
“…In a recently conducted preparatory qualitative study to obtain input to design a structured questionnaire for the current survey, we found that patients with AN mainly associate positive memories and emotions with music (13). The aim of the current research was to further examine the attitudes of people with AN surrounding their use of music, positive and negative effects of music, and their thoughts on music as an adjunct to their treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained were positive and support the use of MT in a daily programme for the treatment of AN. Intervention was found to be feasible and confirms that MT is well received by patients with AN [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 59%
“…Music as a self-regulation tool. Two surveys on the use of and thoughts about music, as an additional therapeutic option in the treatment of AN, were also integrated (Applewhite et al, 2020;Krishna Priya et al, 2021). A total of 46 women and one man between the ages of 18 and 65 who were inpatients or outpatients receiving treatment were surveyed for their opinions.…”
Section: Receptive Mtmentioning
confidence: 99%
“…It can help with recovery and anxiety and it improves ED. In addition, people with AN wish for a MT treatment (Applewhite et al, 2020).…”
Section: Receptive Mtmentioning
confidence: 99%